Seismic Imaging, Fault Damage and Heal. - Li, Yong-Gang (De Gruyter, 2014)
Presenting current approaches in observational and computational seismology, this book introduces advanced methods and techniques by means of case studies in earthquake research. Among others these include solving inverse seismologic problems, tomography for structure imaging, characterizing fault damage and healing, seismicity analysis for determining pre-shock moment release, and coupled solid-fluid models.